Pelatihan Pembuatan Panel Gas Detektor untuk Keselamatan Kerja - Arief Subekti; Edy Prasetyo Hidayat (CV. Creative Tugu Pena, 2024)
In order to implement the community service program, we have carried out activities at SMKN 1 Sidayu, Gresik, with the aim of increasing the capacity and skills of staff, employees and students. During this activity, various training and workshops were held, ranging from developing technical skills to improving soft skills. Active participation from all parties, including staff, employees and students, really supports the smoothness and success of this program. We hope that the results of this service activity can provide long-term benefits for SMKN 1 Sidayu, as well as encourage the progress and development of the institution in the future. Thank you for the cooperation and enthusiasm shown by the entire SMKN 1 Sidayu community during the implementation of this program. Technician competency training is able to design detector control panels. The working mechanism of this gas leak detection device, in principle, involves 3 types of gas sensors with different types as indicators of comparison of sensitivity levels. There were 2 tests carried out, namely using lighter gas and smoke, the type of smoke used was cigarette smoke and lighter smoke with a time limit of 15 seconds. The distance between the gas cylinder and the prototype device is kept close to make it easier for the instrument to detect gas accurately. The gas sensors used are the MQ2, MQ3 and MQ5 gas sensors.